Activities of the Nebraska Research Coordinating Unit for Vocational Education. Final Report - Nebraska Occupational Needs Research Coordinating Unit, Lincoln; Nebraska Occupational Needs Research Coordinating Unit, Lincoln ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1969)
This final report of the Nebraska Research Coordinating Unit for Vocational Education summarizes the activities covered from December 1, 1966 through August 31, 1969. Included in the report are: (1) major activities during the period, (2) problems, (3) significant findings and events, (4) dissemination activities, (5) capital equipment acquisitions, (6) data collection, (7) staff utilization, (8) future activities planned for the next reporting period, and (9) certification. (GR)
Contract Number: OEG-3-7-063032-1620.
Sponsoring Agency: Office of Education (DHEW), Washington, DC. Bureau of Research.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Research Projects; Vocational Education; Educational Research; Occupational Information; Program Descriptions; Research Coordinating Units; State Programs; Nebraska